Decontamination and Reuse of N95 Masks: A Narrative Review - M. A. Khan; A. Ikram; S. Savul; F. K. Lalani; M. A. Khan; M. Sarfraz (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The COVID-19 pandemic has presented an unprecedented strain on healthcare supplies. Currently there is a global shortage of personal protective equipment (PPE), especially N95 masks. In order to safeguard healthcare personnel in this critical time and to mitigate shortages of N95 respirators, reuse of N95 respirators has to be considered. Methods. Using PubMed and Science Direct, a literature search was conducted to find and synthesize relevant literature on decontamination of N95 respirators for their subsequent reuse. Peer-reviewed publications related to methods of decontamination from January 2007 to April 2020 in the English language are included in this narrative review. Bibliographies of articles for relevant literature were also scrutinized. Findings. A total of 19 studies are included in this narrative review. The appraised methods include ultraviolet germicidal irradiation (UVGI), moist heat incubation (MHI), ethylene oxide (EtO), hydrogen peroxide vapor (HPV), microwave steam bags (MSB), microwave-generated steam (MGS), dry microwave oven irradiation, hydrogen peroxide gas plasma (HPGP), dry heat, liquid hydrogen peroxide, and bleach and alcohol. Conclusion. In light of the COVID-19 pandemic, reuse of N95 respirators, although suboptimal, can be considered. Evidence reveals that UVGI, MHI, and HPV are amongst the safest and efficacious methods for decontamination of N95 masks. More research is needed to establish the safety and effectiveness of MGS, MSB, dry heat, EtO, liquid hydrogen peroxide, and HPGP. Alcohol, microwave irradiation, and bleach are not recommended because they damage N95 respirators.